CLASS MANAGEMENT STRATEGIES TO IMPROVE LEARNING MOTIVATION IN ELEMENTARY SCHOOL STUDENTS - Wijaya, Sastra; Marini, Arita; Zulela, Zulela (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
Abstract This research was designed to know classroom management strategies to increase student learning motivation which was carried out by teachers of Mesjid Priyai Elementary School, Serang City. The method used in this research is descriptive qualitative with data collection techniques used in research through observation, interviews, field notes, data recording, literature review, and document analysis to obtain opinions or views regarding the topic under study, documentation, and simple observations of the 30 students of 4th grade as the subjects. Based on the results of the research, shows that the classroom management strategy carried out by the teacher have been going well. It was illustrated by the interaction between the teacher and students, which are running more actively and the teacher can manage the class effectively and efficiently. The teacher has succeeded in presenting a comfortable, safe, and encouraging atmosphere and learning environment for students, which impacted the improvement of student learning motivation. This research recommends that the teachers need to improve their abilities and competencies in classroom management designs based on differentiated learning, the teachers can take part in various training, seminars, and competency improvement workshops, and form teaching teams and teachers' learning communities.                                  Keywords: Class Management; Learning Motivation; Elementary School.